Synergistically enhanced performance of epoxy resin by block copolymer and multi‐walled carbon nanotubes. Issue 26 (21st April 2022) - Zhang, Wei; Cui, Huanan; Lv, Yadong; Yang, Qi; Huang, Yajiang; Li, Guangxian; Kong, Miqiu
Abstract: This work aims to investigate the performance of the epoxy resin modified by poly(ethylene glycol)‐b‐poly(propylene glycol)‐b‐poly(ethylene glycol) (PEO‐PPO‐PEO) block copolymers and multi‐walled carbon nanotubes (MWCNTs). It is detected that when PEO‐PPO‐PEO block copolymers and MWCNTs are simultaneously added, synergistic toughening effects for epoxy resin achieve without loss of other properties. Specifically, with the introduction of 5 wt% PEO‐PPO‐PEO block copolymers, the critical stress intensity factor (KIc ) of the epoxy resin is increased by 65.7% in contrast with the pure epoxy resin by the reason of the epoxy matrix shear yielding triggered by cavitation of PEO‐PPO‐PEO nanophases and by 28.7% with the introduction of 0.25 wt% MWCNTs owing to the pull‐out and crack bridging of MWCNTs, but other properties are decreased. However, with the simultaneous introduction of 5 wt% PEO‐PPO‐PEO and 0.25 wt% MWCNTs, the KIc of epoxy resins is significantly increased by 97.3%, exhibiting much higher than the linear superposition of the corresponding epoxy resin/PEO‐PPO‐PEO and epoxy resin/MWCNTs composites. Meanwhile, the decrease in other properties is retarded. This is because PEO‐PPO‐PEO block copolymer can enhance the interactions between MWCNTs and epoxy resins in the epoxy resin/PEO‐PPO‐PEO/MWCNT composites, thereby promoting the dispersion of MWCNTs in the epoxy resins. Consequently, the fracture toughness of epoxy resins is efficiently boosted by the superposition of the pull‐out and crack bridging of well‐dispersed MWCNTs and the epoxy matrix shear yielding triggered by the strengthened interactions between PEO‐PPO‐PEO block copolymers and MWCNTs. This work supplies an easy and efficient means to solve the dispersion of nanoparticles, which can prominently advance the comprehensive properties of epoxy resins. Abstract :